ENHANCING STAND-ALONE GPS CODE POSITIONING USING STAND-ALONE DOUBLE DIFFERENCING CARRIER PHASE RELATIVE POSITIONING - AMAMI, MUSTAFA M. (Journal of Duhok University, 2017)
Pseudo-range GPS code observables can provide absolute stand-alone positioning with accuracy of a few meters, which may not suitable for a wide range of engineering applications. Differencing GPS observations (DGPS) can be used for reducing or removing some of GPS errors based on the high correlation between these errors over short baselines providing accurate relative positioning. Stand-Alone Double Differences Carrier Phase (SADDCP) is an accurate velocity estimation method based on single frequency stand-alone GPS observables. Precise GPS relative positioning can then be achieved by integrating the velocity over epoch. SADDCP is a double differences technique including two epochs, two satellites and one receiver. In SADDCP, the ambiguity and receiver clock errors are removed, whereas satellite clock error, orbit errors, and ionospheric and tropospheric delays are reduced significantly. Multipath remains and can be reduced based on the multipath correlation over time, and receiver noise is increased. In this paper, SADDCP will be used to enhance the performance of stand-alone GPS code positioning, where the two positioning techniques are integrated using Kalman filter. The precise relative positioning provided by SADDCP will be utilized to smooth the absolute low accurate stand-alone GPS code positioning, providing enhanced absolute single frequency stand-alone GPS positioning. Tests in different GPS environments will be carried out for reliable investigations and the results will be discussed in details showing the advantages and limitations of this integration.